Philippine digital cultures brokerage dynamics on YouTube - Soriano, Cheryll Ruth; Cabalquinto, Earvin Charles (Amsterdam Amsterdam University Press, 2022)
Social media platforms have been pivotal in redefining the conduct of contemporary society. Amid the proliferation of a range of new and ubiquitous online platforms, YouTube, a video-based platform, remains a key driver in the democratisation of creative, playful, vernacular, intimate, as well as political expressions. As a critical node of contemporary communication and digital cultures, its steady uptake and appropriation in a social media-savvy nation such as the Philippines requires a critical examination of its role in the continued reconstruction of identities, communities, and broader social institutions. This book closely analyses the diverse content and practices of amateur Filipino YouTubers, exposing and problematising the dynamics of brokering the contested aspirational logics of beauty and selfhood, interracial relationships, world-class labour, and progressive governance in a digital sphere. Ultimately, Philippine Digital Cultures: Brokerage Dynamics on YouTube offers a fresh, compelling, and nuanced account of YouTube as an important site for the mediation of culture, economy, and politics in Philippine postcolonial modernity amid rapid economic globalisation and digitalisation.
Chapter 1: Lights, Camera, and Click the Notification Bell!, Chapter 2: Digital Brokering, Chapter 3: Self, Chapter 4: Relationships, Chapter 5: Labour, Chapter 6: Politics, Chapter 7: YouTube and Beyond, Index, Bibliography
Keywords: Digital media -- Social aspects; YouTube (Electronic resource); Internet videos -- Political aspects -- Philippines; Online social networks -- Social aspects -- Philippines